2014
DOI: 10.3346/jkms.2014.29.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bladder Cancer among Patients with Diabetes Treated with a 15 mg Pioglitazone Dose in Korea: A Multi-Center Retrospective Cohort Study

Abstract: It has not yet been determined whether chronic exposure to relatively low doses of pioglitazone increases risk of bladder cancer. We aimed to assess the risk of bladder cancer associated with pioglitazone in Korean patients. This was a retrospective cohort study of diabetic patients who had ≥ 2 clinic visits between November 2005 and June 2011 at one of four tertiary referral hospitals in Korea. A prevalent case-control analysis nested within the cohort was conducted to further adjust confounders. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 14 publications
(34 reference statements)
0
40
0
1
Order By: Relevance
“…In addition, some short-term, population-based cohorts in the USA [15], India [23], Japan [24], Korea [25], Taiwan [26,27] and the UK [28] also reported no association between pioglitazone and bladder cancer. In contrast, other short-term, observational database studies have suggested an association between exposure to pioglitazone and incidence of bladder cancer, including a retrospective cohort study using French National Health Insurance Plan data [29], and nested case-control studies in Taiwan [30], the UK [31] and Korea [32].…”
Section: Discussionmentioning
confidence: 94%
“…In addition, some short-term, population-based cohorts in the USA [15], India [23], Japan [24], Korea [25], Taiwan [26,27] and the UK [28] also reported no association between pioglitazone and bladder cancer. In contrast, other short-term, observational database studies have suggested an association between exposure to pioglitazone and incidence of bladder cancer, including a retrospective cohort study using French National Health Insurance Plan data [29], and nested case-control studies in Taiwan [30], the UK [31] and Korea [32].…”
Section: Discussionmentioning
confidence: 94%
“…Again, when I carefully read in a scientific paper that: "a pooled analysis of 25 randomized clinical trials does not indicate that treatment with sitagliptin increases cardiovascular risk in patients with type 2 diabetes mellitus. In a subanalysis, a higher rate of cardiovascular-related events was associated with sulphonylurea relative to sitagliptin" to discover at the end of the paper that "all studies and analyses described in this review were funded by Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Whitehouse Station, NJ" [4] or to read at the end of another similar paper that it was "supported by Merck Sharp & Dohme, a subsidiary of Merck" [5] this simply makes me feel uncomfortable or even suspicious and I don't believe that it's logic not to feel so especially when these results argue with other independent studies [6][7][8].…”
Section: Introductionmentioning
confidence: 66%
“…The included studies were of adequate quality, with more than six stars out of nine in the NOS quality assessment (Table ). Five observational studies were sponsored by industry (Takeda) .…”
Section: Resultsmentioning
confidence: 99%